A mixed‐methods survey to explore views of staff and patients from mental health wards prior to introduction of a digital early warning system for physical deterioration. Issue 3 (22nd March 2019) - Brimblecombe, Neil; Quist, Haddy; Nolan, Fiona
Accessible summary: What is known on the subject?: The potential benefits of introducing technological innovation into all types of health services are recognized internationally. There are few studies exploring the use of technology in inpatient mental health settings, or the views of staff and patients regarding such developments. "Early warning systems" are increasingly used in inpatient mental health services to detect physical deterioration in patients and prompt staff to take appropriate action. We have identified no peer‐reviewed publications concerning this development. What the paper adds to existing knowledge?: Using a questionnaire survey, this project gathered views from staff and patients on a planned change from a paper‐based "early warning system" to one using handheld electronic devices (tablets). This study adds to the existing evidence by reporting specific staff and patient concerns about a technological development in an inpatient mental health setting. Some patients were concerned about confidentiality of data entered onto tablets. Whilst were either positive or neutral in attitude to the planned change some staff raised concerns that electronic devices could be used as weapons, and also that patients or visitors might misinterpret their use. What are the implications for practice?: Views of staff and patients must be considered when introducing new technology into clinical practice, in order to make the change successful and sustainable. Inadequate or unclear information about the use and purpose of electronic devices may lead to misunderstandings as to their purpose and the security of their data, particularly in mental health settings. Further exploration across a range of services and countries would be useful in determining whether attitudes towards implementing similar technological change in mental health practice are commonly shared. Abstract: Introduction: Technological innovation offers opportunities to improve mental health care; however, little evidence exists regarding attitudes of inpatient staff and patients to such changes. We present a survey of staff and patients prior to introduction of a digital version of the National Early Warning Score (eNEWS) system for identifying physical deterioration. Aim: To collate views of staff and inpatients related to prospective use of eNEWS, to inform the plan for implementation. Method: Paper questionnaires were distributed to both groups in six wards prior to eNEWS implementation. Two discussion groups were then held. Results: Eighty‐two staff and 26 inpatients completed questionnaires. Some inpatients expressed concerns about data confidentiality. Most staff were neutral or positive about the planned change, but raised possible safety risks and the risk of electronic recording being misinterpreted by patients. The implementation plan was modified in response to this information, principally by improving communication processes with patients. Discussion: This study adds to the existing evidence by reporting specific staff and patient concerns towards a form of information technology. Further evaluations would help determine the transferability of these findings. Implications for practice: Listening to patient and staff views about planned technological innovation is essential for effective implementation.